Amitozyn impairs chromosome segregation and induces apoptosis via mitotic checkpoint activation. - Bastien Hermant; Aldrian Gudrun; Anatoly I Potopalsky; Jadwiga Chroboczek; Sergey O Tcherniuk (PLoS ONE, 2013)
Amitozyn (Am) is a semi-synthetic drug produced by the alkylation of major celandine (Chelidonium majus L.) alkaloids with the organophosphorous compound N,N'N'-triethylenethiophosphoramide (ThioTEPA). We show here that the treatment of living cells with Am reversibly perturbs the microtubule cytoskeleton, provoking a dose-dependent cell arrest in the M phase. Am changed the dynamics of tubulin polymerization in vitro, promoted the appearance of aberrant mitotic phenotypes in HeLa cells and induced apoptosis by the activation of caspase-9, caspase-3 and PARP, without inducing DNA breaks. Am treatment of HeLa cells induced changes in the phosphorylation of the growth suppressor pRb that coincided with maximum mitotic index. The dose-dependent and reversible anti-proliferative effect of Am was observed in several transformed cell lines. Importantly, the drug was also efficient against multidrug-resistant, paclitaxel-resistant or p53-deficient cells. Our results thus open the way to further pre-clinical evaluation of Am.